Application and best practices of new communication technology: a case study of Tourism Malaysia 2014 / Nurul Diana Jasni ... [et al.] - Jasni, Nurul Diana; Che Zainal, Che Nur Amalina S.; Abd Latiff, Zulkifli (2014)
The Ministry of Tourism and Culture Malaysia has integrated the use of new communication technologies in the department as well as in promoting Visit Malaysia 2014 (VMY2014). The tourism plays an important role in the growth of the economy and putting Malaysia in the world map. In particular, this study measures 1) to explore application and best practices of new communication technologies by Information Management Division in Ministry of Tourism and Culture, 2) to examine new communication technologies used by Tourism Malaysia in Promoting “Visit Malaysia 2014” campaign. Case study method was use in the study as it is a systematic gathering of enough information about a particular organization to allow the researcher insight into the life of that organization. This research will contribute to the extension of knowledge in improving application of new communication technologies by Tourism Malaysia. The use of new communication technology in the department has built the bonding between the staff as there are two ways of communication applied. The Information Management Division under the Ministry has equipped the department with the latest hardware and software to the community. Besides that, there is also the increasing number of receipt and tourist coming to Malaysia compared to the year 2013. It shows the successfulness of new communication technology engage by the Tourism Malaysia in attracting people to come to Malaysia.